Verapamil and beta cell function in adults with recent-onset type 1 diabetes - Ovalle, Fernando; Grimes, Tiffany; Xu, Guanlan; Patel, Anish J.; Grayson, Truman B.; Thielen, Lance A.; Li, Peng; Shalev, Anath (Nature medicine, 2018)
Pancreatic beta cell loss is a key factor in the pathogenesis of type 1 diabetes (T1D), but therapies to halt this process are lacking. We previously reported that the approved antihypertensive calcium-channel blocker verapamil, by decreasing the expression of thioredoxin-interacting protein, promotes the survival of insulin-producing beta cells and reverses diabetes in mouse models 1 . To translate these findings into humans, we conducted a randomized double-blind placebo-controlled phase 2 clinical trial ( NCT02372253 ) to assess the efficacy and safety of oral verapamil added for 12 months to a standard insulin regimen in adult subjects with recent-onset T1D. Verapamil treatment, compared with placebo was well tolerated and associated with an improved mixed-meal-stimulated C-peptide area under the curve, a measure of endogenous beta cell function, at 3 and 12 months (prespecified primary endpoint), as well as with a lower increase in insulin requirements, fewer hypoglycemic events and on-target glycemic control (secondary endpoints). Thus, addition of once-daily oral verapamil may be a safe and effective novel approach to promote endogenous beta cell function and reduce insulin requirements and hypoglycemic episodes in adult individuals with recent-onset T1D. A phase 2 placebo-controlled randomized trial reveals that verapamil promotes beta cell function in adult subjects with recent-onset type 1 diabetes.